Strategies for preservation of and open access to scientific data in China : summary of a workshop - Uhlir, P. F. (Paul F.), 1954-; Esanu, Julie M. (National Academies Press, 2006)
Preservation of and open access to digital scientific resources are essential to global research, yet the challenges in storing and maintaining access to these collections are substantial. China faces major hurdles in this regard. A workshop held in June 2004 in Beijing convened scientific information managers, digital archiving experts, national science policy and funding officials, and representatives of development organizations to explore the scientific and technical, legal and policy, institutional and economic, and management aspects of creating sustainable and accessible archives of digital health and environmental data in China.